Dialogic Learning in Interactive Groups - M. Josepa Adell Nolla; Carlos Herrero; Belinda Siles (Networks: An Online Journal for Teacher Research, 2004)
This jointly written article is the attempt to share with other teachers, teacher trainers, other professionals and participants in the field of education, our experiences with interactive groups. It brings new meaning to our work to see children infused with hope, enthusiasm and purpose in the classroom since we have begun this egalitarian educational practice. The joy and fulfilment we are seeing and experiencing is contagious. We feel that to bring to light innovations that are working in the classroom and school is fundamental for all of us in our profession as we take on the responsibility, along with parents and other community members, of accompanying children on part of their journey in the learning process. We hope that these exchanges, can help us to move step by step together towards overcoming social, educational and economic inequalities, and assuring every child's participation in the knowledge society.